2016
DOI: 10.1073/pnas.1605516113
|View full text |Cite
|
Sign up to set email alerts
|

Land-use and climate change risks in the Amazon and the need of a novel sustainable development paradigm

Abstract: For half a century, the process of economic integration of the Amazon has been based on intensive use of renewable and nonrenewable natural resources, which has brought significant basin-wide environmental alterations. The rural development in the Amazonia pushed the agricultural frontier swiftly, resulting in widespread land-cover change, but agriculture in the Amazon has been of low productivity and unsustainable. The loss of biodiversity and continued deforestation will lead to high risks of irreversible ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
508
0
68

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 701 publications
(589 citation statements)
references
References 184 publications
(185 reference statements)
13
508
0
68
Order By: Relevance
“…Indeed, Khanna et al [13] suggested that deforestation is sufficiently advanced to have caused a shift from a thermally-to a dynamically-driven climatic regime, which may affect the rainy season in the future. In this connection, previous studies have pointed to intensification of the dry season in the southern Amazon [15][16][17], and predicted intensification of rainfall during the rainy season [18] or changes in the wet-day and dry-day frequencies [19].…”
Section: Introductionmentioning
confidence: 71%
See 2 more Smart Citations
“…Indeed, Khanna et al [13] suggested that deforestation is sufficiently advanced to have caused a shift from a thermally-to a dynamically-driven climatic regime, which may affect the rainy season in the future. In this connection, previous studies have pointed to intensification of the dry season in the southern Amazon [15][16][17], and predicted intensification of rainfall during the rainy season [18] or changes in the wet-day and dry-day frequencies [19].…”
Section: Introductionmentioning
confidence: 71%
“…The intense land use changes, mainly characterized by high deforestation rates, that have taken place in this pioneer active frontier region in the last four decades partly explain the observed trend toward increased seasonality [20] and a shortening of the rainy season [16,17]. Such trends may have irreversible ecological impacts [44] and affect agricultural activities, which depend on the quantity of rainfall and temporal patterns [15,[47][48][49]. …”
Section: Study Areamentioning
confidence: 98%
See 1 more Smart Citation
“…Sulfur-laden oil and diesel are the historical fuels. The Amazon region is of vital importance for the functioning of both regional ecosystems and climate (Fisch et al, 1998;Nobre et al, 2016). Topics for research in recent years have included the relationship between the biosphere and the atmosphere in the Amazon (Fan et al, 1990;Stark et al, 2015); the impacts of land use change (Dickinson and Kennedy, 1992;Fearnside, 2003;Paula et al, 2014;WertzKanounnikoff et al, 2016); and the consequences of urbanization, population growth, and increased anthropogenic emissions to the composition of the atmosphere (Shukla et al, 1990;Potter et al, 2001;Wright, 2005;Malhi et al, 2008;Martin et al, 2016).…”
mentioning
confidence: 99%
“…Several studies have projected that land use and climate conditions of tropical regions in the future are generally characterized by a continuous reduction of tropical forest area due to cropland expansions, an increase in the average temperature (similarly to all regions in the world) and changes in the spatial and temporal precipitation variability at an uncertain magnitude (Thomson et al, 2010;Wohl et al, 2012;Nobre et al, 2016). As a result, the frequencies of droughts and floods in tropical regions related to land use and climate change are predicted to increase, resulting in threats to local or regional socio-economic development (IPCC, 2007;.…”
Section: Introductionmentioning
confidence: 99%